Atmospheric residence times and excess of unsupported 210Po in aerosol samples from the Kuwait bay-northern gulf. (December 2020) - Aba, A.; Ismaeel, A.; Al-Boloushi, O.; Al-Shammari, H.; Al-Boloushi, A.; Malak, Mariam
Abstract: The concentration of cosmogenic radionuclide 7 Be and the naturally occurring radionuclide 222 Rn and its progenies 210 Pb, 210 Po, and 214 Pb were measured in the ground surface air in the urban area of the northern Arabian Gulf close to Kuwait Bay. A high-volume air sampler connected with a five-stage cascade impactor was used to collect approximately 1800 cubic meter weekly for a period of one year. The concentrations of 210 Pb and 210 Po varied from 0.35 to 1.65 mBq m −3 and from 0.23 to 3.2 mBq m −3, respectively; the 210 Po/ 210 Pb activity ratio was close to one. The average concentration of 7 Be was 6.24 mBq m −3, ranging from 3 to 10 mBq m −3 . The temporal variations of 210 Pb, 210 Po and 7 Be showed maximum concentrations of 210 Po and 7 Be in occurred summer months. The observed excess of 210 Po concentrations can be attributed to the local and long-range transport of suspended dust with 210 Pb and 210 Po in radioactive equilibrium state, oil industry emissions, local resuspended dust and the sea-salt-aerosols from the Arabian Gulf. The range of the residence time estimation using the 222 Rn/ 210 Pb and 214 Pb/ 210 Pb activity ratio methods ranged from three to five days. Moreover, the estimated residence time by the application of 7 Be from the activity median aerodynamic diameter method was 4.2 days. The method of using the 210 Po/ 210 Pb activity ratio was invalid because of the excess 210 Po sources of anthropogenic origin. Therefore, extensive accurate diurnal measurements of 214 Pb and 222 Rn can be applied in hot arid regions for better aerosols residence time estimation. Highlights: Radioactive aerosol residence time was examined in the northern Arabian Gulf. The estimated mean aerosols residence time varied from 3 to 5 days. 210 Po/ 210 Pb activity ratios are inapplicable in the northern Arabian Gulf. Excess 210 Po concentrations are to the local and long-range transport of suspended dust.